Cardiovascular autonomic functions & cerebral autoregulation in patients with orthostatic hypotension - Khandelwal, Ekta (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND & OBJECTIVES: Patients of orthostatic hypotension may or may not have symptoms of the cerebral hypoperfusion despite fall in the blood pressure. The present study was done to quantify autonomic functions and cerebral autoregulation in patients of orthostatic hypotension with or without symptoms. METHODS: The study was conducted in 15 patients of orthostatic hypotension and 15 age, sex matched control subjects. The sympathetic reactivity was measured by diastolic blood pressure response to handgrip test (ΔDBP in HGT) and cold pressor test (ΔDBP in CPT). The parasympathetic reactivity was measured by E:I ratio during deep breathing test (DBT) and Valsalva ratio (VR) during Valsalva maneuver. The cerebral autoregulation was computed from the changes in the cerebral blood flow, cerebrovascular conductance and blood pressure measured during different time points during head-up tilt (HUT). RESULTS: The sympathetic reactivity was lower in patients as compared to controls [ΔDBP in HGT: 10 (4 - 16) vs 18 (12 - 22) mmHg, P<0.01; ΔDBP in CPT : 10 (4-12) vs 16 (10-20) mmHg, P<0.01]. The parasympathetic reactivity was also lower in patients as compared to controls. The sympathetic and parasympathetic reactivity was comparable in the symptomatic and asymptomatic patients. The maximum fall in blood pressure during HUT was comparable between symptomatic and asymptomatic patients (29.14 ± 10.94 vs 29.50 ± 6.39 mmHg), however, the percentage fall in the cerebral blood flow was significantly higher in the symptomatic (P<0.05) compared to asymptomatics. INTERPRETATION & CONCLUSIONS: Patients with orthostatic hypotension had deficits in sympathetic and parasympathetic control of cardiovascular system. Cerebral autoregulation was present in asymptomatic patients (increase in cerebrovascular conductance) during HUT while it was lost in symptomatic patients.